RETRACTION NOTE: Effect of curcumin on hippocampus dentate gyrus injury induced by nicotine in rats - Cyrus Jalili; Babak Arji Rodsari; Shiva Roshankhah; Mohammad Reza Salahshoor (Shahrekord University of Medical Sciences, 2022)
This paper was published in the Journal of Herbmed Pharmacology in 2019 (doi: 10.15171/jhp.2019.47) (1). Based on an email received from the team of young researchers recently, we were informed that the results of this article (some figures and diagrams) have been published in several similar articles (2-5), which are considered ethical misconduct. This issue was investigated by the editorial team of the Journal of Herbmed Pharmacology. As a result, based on the Committee on Publication Ethics (COPE) guidelines, the editors decided to retract this paper. The authors were informed and advised on this serious ethical breach. This article has been retracted at the request of the corresponding author. The retracted article will remain online to maintain the scholarly record, but it will be watermarked on each page as 'retracted'. References 1.Jalili C, Arji Rodsari B, Roshankhah S, Salahshoor MR. Effect of curcumin on hippocampus dentate gyrus injury induced by nicotine in rats. J Herbmed Pharmacol. 2019;8(4):320-327. doi: 10.15171/jhp.2019.47. 2.Roshankhah S, Abdolmaleki A, Jalili C, Salahshoor MR. Ameliorative Effect of Falcaria vulgaris on Nicotine-induced Injury on the Hippocampus Dentate Gyrus Region of Rats. Int J Pharm Invest. 2019;9(4):200-204. 3.Roshankhah S, Jalili C, Salahshoor MR. Falcaria vulgaris attenuates morphine toxicity in prefrontal cortex in rats. Egyptian Pharmaceutical Journal. 2019;18:276-84. doi: 10.4103/epj.epj_18_19. 4.Roshankhah S, Sadeghi E, Jalili C, Salahshoor MR. Impacts of Low‑Protein Diet on the Hippocampal CA1 Neurons and Learning Deficits in Rats. Adv Hum Biol. 2019;9:124-8. doi: 10.4103/AIHB.AIHB_31_19. 5.Salahshoor MR, Abdolmaleki A, Roshankhah S, Jalali A, Jalili C. Curcumin recovers the toxic effects of nicotine on hippocampus cornu ammonis 1 in rats. J Pharmacol Pharmacother. 2019;10:85-92. doi: 10.4103/jpp.JPP_38_19.